prove this question
Attachments:
![](https://hi-static.z-dn.net/files/d7d/4e979f6c80ed2df0e30b77cdbc9b11c3.jpg)
Answers
Answered by
0
Answer:
HOPE IT HELPS YOU !!!!!!!
Step-by-step explanation:
Now,
3sinθ + 5cosθ=5
=> (3sinθ+5cosθ)²=(5)²
=> 9sin²θ+25cos²θ+30sinθcosθ=25
=>9 (1 - cos²θ) + 30 sinθ cosθ + 25 (1 - sin²θ) = 25
=>9 - 9 cos²θ + 30 sinθ cosθ + 25 - 25 sin²θ = 25
=>25 sin²θ - 30 sinθ cosθ + 9 cos²θ = 9
=>(5 sinθ - 3 cosθ)² = 3²
=>5 sinθ - 3 cosθ = ±3 [ proved]
THANK YOU
MARK AS BRAINLIEST
Similar questions